A functional XopAG homologue in Xanthomonas fuscans pv. aurantifolii strain C limits host range. (11th March 2015) - Gochez, A. M.; Minsavage, G. V.; Potnis, N.; Canteros, B. I.; Stall, R. E.; Jones, J. B.
Abstract : Citrus canker is caused by two Xanthomonas species, Xanthomonas citri, which has become the primary pathogen where citrus canker occurs (type A citrus canker, Xc‐A), and X. fuscans pv. aurantifolii (Xfa), which consists of strains B and C. The B strain is less pathogenic than the A strain, but produces symptoms in all citrus species. The C‐type cankers only infect Key lime ( Citrus aurantifolia ) and produce a hypersensitive reaction (HR) in grapefruit ( Citrus paradisi ) leaves. An avirulence gene, avrGf2, was identified in a C strain that was responsible for the HR in grapefruit. AvrGf2 is a member of XopAG effector family and shares 45% identity at amino acid level with another member of the same family, AvrGf1 from strain Xc‐A w, which was previously shown to elicit an HR in grapefruit. AvrGf2 shares sequence identity with other XopAG effectors present in Xanthomonas vasculorum, Xanthomonas campestris pv. musacearum and Pseudomonas syringae pv. tomato . Mutagenesis of avrGf2 in C strain resulted in a compatible reaction in grapefruit. There was no observable effect on virulence when Xc‐A transconjugants containing either avirulence gene were inoculated on Key lime. Expression of avrGf1 or avrGf2 in Xc‐A resulted in a similar phenotype following infiltration into grapefruit leaves, although the avrGf2 transconjugant elicited a faster HR and lower populations than the transconjugant containing avrGf1 . Also, it was shown that all Xfa‐B strains tested contain a transposon in avrGf2 that helps to explain the differences in host range between B and C strains.